4x+6=12-5x

Simple and best practice solution for 4x+6=12-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+6=12-5x equation:


Simplifying
4x + 6 = 12 + -5x

Reorder the terms:
6 + 4x = 12 + -5x

Solving
6 + 4x = 12 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
6 + 4x + 5x = 12 + -5x + 5x

Combine like terms: 4x + 5x = 9x
6 + 9x = 12 + -5x + 5x

Combine like terms: -5x + 5x = 0
6 + 9x = 12 + 0
6 + 9x = 12

Add '-6' to each side of the equation.
6 + -6 + 9x = 12 + -6

Combine like terms: 6 + -6 = 0
0 + 9x = 12 + -6
9x = 12 + -6

Combine like terms: 12 + -6 = 6
9x = 6

Divide each side by '9'.
x = 0.6666666667

Simplifying
x = 0.6666666667

See similar equations:

| 2k^2+6k+9=0 | | 2x+(x-20)+x=180 | | 2k^2+6k=-9 | | 6b+2t=232 | | 4(2+1)=2(3-x) | | 26=-16x^2+4x+16 | | 5p+7=3(4-q) | | 4n-5=3 | | x*x-18x+81=4+81 | | -14=-(-2+2) | | -x*x+x+.25=1.25 | | 2m+6=2(2m+3)-2 | | -x*-x+x+.25=1.25 | | 3(c-8)+13=5c+5 | | -4.4=2x+25.6 | | 4.2z=-4(0.6-1.2) | | 2mx^2-mx+1=0 | | 3(6-x)-8=2 | | 5x+6x-64=3x-65 | | 4v-2=10 | | 5x^2=2x+1 | | 6x+19x=25 | | 4x+2+6x-1=13x+1 | | 18-6y=0 | | 4x+3=42 | | 10=3f+1 | | 2b+1=7 | | 4x-5=-1x-30 | | -2x-10+7x=6x+14-4x | | x+14=-32-9 | | -6y+13=-5(y-4) | | 13x=-7-3-20 |

Equations solver categories